Loss of Biodiversity Dimensions through Shifting Climates and Ancient Mass Extinctions. (10th September 2018) - Edie, Stewart M; Huang, Shan; Collins, Katie S; Roy, Kaustuv; Jablonski, David
Abstract: Many aspects of climate affect the deployment of biodiversity in time and space, and so changes in climate might be expected to drive regional and global extinction of both taxa and their ecological functions. Here we examine the association of past climate changes with extinction in marine bivalves, which are increasingly used as a model system for macroecological and macroevolutionary analysis. Focusing on the Cenozoic Era (66 Myr ago to the present), we analyze extinction patterns in shallow-water marine bivalve genera relative to temperature dynamics as estimated from isotopic data in microfossils. When the entire Cenozoic timeseries is considered, extinction intensity is not significantly associated with the mean temperature or the detrended variance in temperature within a given time interval (stratigraphic stage). However, extinction increases significantly with both the rate of temperature change within the stage of extinction and the absolute change in mean temperature from the preceding stage to the stage of extinction. Thus, several extinction events, particularly the extinction pulse near the Pliocene–Pleistocene boundary, do appear to have climatic drivers. Further, the latitudinal diversity gradient today and the Cenozoic history of polar faunas suggest that long-term, regional extinctions associated with cooling removed not just taxa but a variety of ecological functions from high-latitude seas. These dynamics of biodiversity loss contrast with the two mass extinctions bracketing the Mesozoic Era, which had negligible effects on the diversity of ecological functions despite removing nearly as many taxa as the latitudinal gradient does today. Thus, the fossil record raises a key issue: whether the biotic consequences of present-day stresses will more closely resemble the long-term effects of past climate changes or those that cascaded from the mass extinctions.